The uncertain Lord Don Oedipus (!), Prince of... Galicia? Hypertextual and contextual relationships in Don Hamlet by Álvaro Cunqueiro - de León, Aguilar Armando T. (Romanica Olomucensia, 2024)
O incerto señor Don Hamlet, príncipe de Dinamarca ('The uncertain Lord Don Hamlet, prince of Denmark', 1958) is the first play by Álvaro Cunqueiro and the first widely recognised tragic work in the Galician literary system. This inaugural drama focuses on the interaction scheme of Shakespeare's plot in the light of Freudian theories - having the myth of Oedipus in the background - and contains a series of veiled socio-historical meanings referring to the context of its production: Galicia under the Franco dictatorship. Therefore, Cunqueiro's play was analysed from a double perspective: hypertextual and contextual. The former highlights the author's literary work, the latter, the socio-historical contents that some components of the play insinuate. Thus, the dramatic syntax of Don Hamlet was appreciated, while glimpsing its semantic and ideological charge. Among the results presented in this paper is the confluence in the dramatic framework of two aspects of the tragic tradition: the Elizabethan, which is evident from the title, and the Attic, whose representative mythemes appear as the action, which ends in a properly Freudian conflict, runs. The dense and hostile atmosphere in which the characters interact has contextual implications. In a literary system such as the Galician one, which lacks antecedent tragic production, O incerto señor Don Hamlet constitutes a landmark because of both its avant-garde dramatic technique and the conditions - Franco's repression - in which it is set. Moreover, it is a good example of the derivations of the tragic genre into which parodic procedures are incorporated.
Keywords: tragic rewritings; text and context; Galician theatre and Francoism; Oedipus and Hamlet; tragedy and avant-garde